2019
DOI: 10.11604/pamj.2019.34.22.15642
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between occupational burnout and demographic variables among nurses in Jahrom, Iran

Abstract: IntroductionOccupational burnout is a psychological syndrome caused by the accumulation of work-related stress and characterized by intolerance, high levels of emotional exhaustion, depersonalization, and the perception of low personal accomplishment. The present study aimed to evaluate the relationship between occupational burnout and all demographic variables among the nurses in Jahrom, Iran.MethodsThe present descriptive-analytical study was carried out during 2016 among nurses employed at Motahari Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…Income is also reported to affect burnout scores. 24 The results in our study were consistent with that; a decrease in monthly income increased the DP scores of the students. Another significant predictor of burnout was the living situation of the student.…”
Section: Discussionsupporting
confidence: 92%
“…Income is also reported to affect burnout scores. 24 The results in our study were consistent with that; a decrease in monthly income increased the DP scores of the students. Another significant predictor of burnout was the living situation of the student.…”
Section: Discussionsupporting
confidence: 92%
“…These factors have been related to feelings of diminished accomplishment. 35,36 Furthermore, medicine has a clear hierarchy where large discrepancies exist in both tangible (eg, pay) and nontangible (eg, respect) aspects of the work environment between clinicians and nonclinicians. [36][37][38] These differences may explain why nonclinical professionals experience diminished accomplishment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Yektatalab et al. (2019) examined 250 nurses working in Iranian health facilities and the percentages of the above three burnout subscales are 25.2%, 12.4% and 52%, respectively. Conversely, another study conducted on orthopaedic nurses in Italy, revealed that the incidence of high level emotional exhaustion (66%) and depersonalization (83%) are much higher than the results of this study, but the rate of diminished sense of personal achievement (88%) is lower (Martinelli et al., 2019).…”
Section: Discussionmentioning
confidence: 99%